Factors affecting acceptance of “E-Pelarian Cukai” system among Malaysians - Subin, Ilin (2024)
“E-Pelarian Cukai,” also known as the tax evasion reporting system, was launched on January 1st, 2023, and the cases reported as of September 2023 were 2829 cases. The objective of this study is to examine factors affecting the acceptance of the “E-Pelarian Cukai” system among Malaysians by using the Technology Acceptance Model (TAM). Variable factors such as perceived usefulness (PU), perceived ease of use (PEOU), reward (RW), and awareness (AW) will be tested to determine if they influence the acceptance of this system. Drawing on the quantitative research method, 329 usable responses were collected through an online survey form. 23.7% of the usable responses were familiar with the system, while 76.3% never used the system yet. By using SmartPLS to run the test, the results show that perceived usefulness and perceived ease of use significantly influence the acceptance of the “E-Pelarian Cukai” system among Malaysians. While reward and awareness are also a crucial factor for the acceptance of this system. The Inland Revenue Board of Malaysia (IRBM) should integrate robust rewards into the system, which is believed to increase user satisfaction and overall system acceptance. The design of these programs should align with the preferences and needs of IRBM as required by policymakers in terms of tax collection in the country, besides investing in targeted initiatives to increase awareness about the "E-Pelarian Cukai" system.